REHABILITATION OF A CYSTIC MIXED DENTITION MANDIBLE FOLLOWING MARSUPIALIZATION WITH A MULTIPURPOSE ACRYLIC SPLINT ACTING AS A SPACE MAINTAINER AND AN OBTURATOR - Nawaz, Nawaz MS; Yazdanie, Yazdanie N; Faheemuddin, Faheemuddin M (Journal of Ayub Medical College Abbottabad, 2011)
Radicular cysts are the most common odontogenic cystic lesions of inflammatory origin which can be managed by marsupialisation specially if the cyst is large and is in relation to the vital structures. This article presents a case in which a radicular cyst was present in association with grossly carious deciduous molars and has been treated by marsupialisation. Postoperatively a surgical splint was inserted to maintain the patency of the bone cavity. This obturator splint also acts as a space maintainer to prevent space loss and ensure unimpeded eruption of permanent premolars. Keywords: Marsupialisation, Space Maintainer, Obturator, Mandibular Splint, Mix Dentition Stage, Radicular cyst